Analysis of Human Resource Management Policies and Their Impact on the Civil Service in Iraq (A field study in the Iraqi Health Administration) - Ali, Ali Saadoon (Journal of Economics and Administrative Sciences, 2020)
This research aims to analyze and the impact of human resourcemanagement policies (as an independent variable) contained in the public sectorreform program on the civil service (as a dependent variable). The importance ofthe research lies in the implementation and implementation of various projects inthe reform groups of the public sectors and the human resource managementsystem in particular, By analyzing the administration’s trends and policies,identifying all strengths, working to improve and increasing its efficiency rates,working to identify, fix and remove all weaknesses, as well as working to replacethem with strengths, and then work to develop resources in more than one form,especially human resources The research problem was also represented in findingthe knowledge that the Iraqi state carries out in determining all theadministrative foundations used in human resources and how to integrate theminto the public health sector, in order to achieve and organize the social reformprogram that the state aims to achieve using the various civilized and widespreadmethods spread around the world to improve the field services provided Forindividuals without discrimination or racism, as it works to improve the role ofhuman resources and take care of the main pillar present in it and expressed in it,through the evaluation and evaluation of the human element using the criteria ofequality and equal opportunities, control and transparency, and to clarify therelationship between the research variables, the descriptive analytical approachwas used in the study To renew the effects of human resources management andthe policies used in the public sector, where the number of the sample used was160 individuals as an experimental sample. One hundred (100) individuals werephysicians, and sixty (60) nurses were in (7) hospitals, including governmentaland some private, and the data were analyzed. In the statistical program (spss)and (Excel), using a number of statistical methods, including (arithmetic mean,mean deviation (Yari, Alpha Crow Nbach Factor, Pearson Correlation) Theresearch has reached many results, the most important of which are identifyingthe different trends in each of them, the integrity and efficiency provided inidentifying the different actors between different organizations andestablishments, as well as the trends for human development resources and thedevelopment programs responsible for that.